Taking stock of Australia’s asymmetrical relations with China: interdependence, tensions, and new dimensions - Kizeková, Alica (2021)
This article deals with the asymmetrical relations between Australia and China and explores their interdependence, tensions, and societal outlooks. Both countries are dependent on one another for trade to different degrees but attempt to diversify their supply chains. While there is no united position on China in Australia, there has been a bipartisan support for the counter-interference legislation there. The newly established security pact of the United States (US), the United Kingdom (UK) and Australia – ‘AUKUS’ – has brought a new dimension into these tensions and will most likely lead to an arms race. The author explores how a so-called middle power such as Australia balances the related economic and strategic interests and priorities. Although Australia has been vulnerable in its asymmetric relationship with China, it has shown that it is not a passive and helpless actor when facing an economic coercion. The interdependence has become a moderating factor in this strategic stand-off. Additionally, Australia demonstrates its tendency to reinforce its traditional reliance on its previous more powerful allies, the UK and the US.